Early immune mechanisms of neonatal porcine islet xenograft rejection. (13th August 2019) - Mok, Dereck; Black, Mazzen; Gupta, Nancy; Arefanian, Hossein; Tredget, Eric; Rayat, Gina R.
Abstract: Background: Neonatal pigs have the potential to provide an inexhaustible source of islets for the treatment of type 1 diabetes. However, the immunological barriers to islet xenotransplantation still need to be overcome. A better understanding of the xeno‐specific immune responses that are involved in neonatal porcine islet (NPI) xenotransplant rejection will help to facilitate the identification of new targets for anti‐rejection therapies, and thus enable more specific targeting of the immune cells and molecules involved. Methods: In this study, we examined the early events of NPI xenograft rejection in the absence of autoimmunity using an immune‐competent B6 mouse transplant model. Immune cells were identified by immunohistochemistry and immune molecules were identified by reverse transcription‐PCR and flow cytometry assays. Results: Our results demonstrated that early events in NPI xenograft rejection are characterized by initial infiltration of innate immune cells such as macrophages (M1) and neutrophils. Conclusions: Targeting these cells, which appear early in the rejection process, may provide an opportunity to abort the rejection process prior to activation of T cells. One strategy could be the blockade of chemotactic signals associated with preferential recruitment of immune cells into the graft site. Collectively, our studies demonstrated that early recruitment of immune cells into graft site is controlled by chemotactic activities and suggest a potential target to prevent the early infiltration of immune cells within the graft. Our findings in this study will have significance in improving NPI xenograft acceptance and induce long‐term xenograft survival.